2012
DOI: 10.1007/s00340-012-4905-0
|View full text |Cite
|
Sign up to set email alerts
|

Model calculation of amplitudes for FT-ICR ion detection in a cylindrical Penning trap

Abstract: A Green's function strategy first proposed by Grosshans et al. is used to calculate the electric charges induced by trapped ions on the 4-fold or 8-fold segmented ring electrode of a cylindrical Penning trap. The ions are assumed to move in the central region of the trap where the harmonic approximation holds. The electric charges induced on each detection segment of the ring electrode are obtained in the form of a triple Fourier series with coefficients that describe the contribution of each frequency combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Theoretical investigations by Kretzschmar contribute for example to the understanding of the frequency shifts due to space charge and to a model of signal intensities, including explanation of sidebands in a cylindrical ICR cell …”
Section: Fourier Transform Ion Cyclotron Resonance Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical investigations by Kretzschmar contribute for example to the understanding of the frequency shifts due to space charge and to a model of signal intensities, including explanation of sidebands in a cylindrical ICR cell …”
Section: Fourier Transform Ion Cyclotron Resonance Msmentioning
confidence: 99%
“…Theoretical investigations by Kretzschmar contribute for example to the understanding of the frequency shifts due to space charge and to a model of signal intensities, including explanation of sidebands in a cylindrical ICR cell. 63,64 For high precision physical measurements it may be important to reach a near-ideal Penning (ie, quadrupolar) potential, despite other limitations on the geometry. For example, a Gabrielse-type 65 Penning trap is further optimized for laser beam access and used with FT-ICR detection for fragmentation analysis.…”
Section: Icr Cellsmentioning
confidence: 99%
“…Possible signals are expected for each frequency combination n + ν + + n − ν − + n z ν z (n i positive or negative integer or 0). Using the computational method proposed by Grosshans et al [27] it can be shown that the Fourier coefficient belonging to n + ν + + n − ν − is proportional to (R + /a) n + (R − /a) n − (up to small corrections of order (R ± /a) 2 ), where a denotes the radius of the cylindrical trap [28]. Thus, in leading order the Fourier amplitude for the signal at the modified cyclotron frequency ν + is proportional to R + .…”
Section: Amplitudes Of Ft-icr Signalsmentioning
confidence: 99%
“…The trapped ion induces oscillating image charges on the surrounding trap electrodes. While these induced image charges are essential for the detection of the ion's oscillation frequencies [19][20][21][22], they cause a systematic shift to the ion's frequencies by generating an undesired electrostatic field E image , which acts back on the ion and slightly shifts the ion's eigenfrequencies; see Fig. 2.…”
Section: Image Charge Shiftmentioning
confidence: 99%